2009
DOI: 10.1111/j.1461-9563.2009.00428.x
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal abilities of adult click beetles in arable land revealed by analysis of carbon stable isotopes

Abstract: 1 The dispersal abilities of agrioted beetles, serious pests on a variety of crops, are poorly known under natural conditions. This hampers their control. We used, for the first time, a stable isotope approach to assess dispersal of adult Agriotes obscurus in arable land. 2 After a diet switch from a C3-to a C4-plant, carbon isotope ratios of A. obscurus larvae significantly changed towards the isotopic signature of the new diet. Moreover, the larval ␦ 13 C signatures were transferred to the wing covers of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 25 publications
2
47
1
Order By: Relevance
“…The management of the environment may focus on the habitat, farm or landscape levels (Landis et al 2000), with scale-dependent effects on natural enemies (Tscharntke et al 2007). Stable isotope ratios have been proven to be suitable for tracking the plant origin of herbivorous and predatory insects Vialatte et al 2006;Traugott et al 2008;Schallhart et al 2009Schallhart et al , 2011Forbes and Gratton 2011;Ouyang et al 2012). Recently, this method has been used to determine the dispersal of pest predators between alfalfa and maize in the northeast of the Iberian Peninsula (Madeira et al 2014).…”
Section: Introductionmentioning
confidence: 98%
“…The management of the environment may focus on the habitat, farm or landscape levels (Landis et al 2000), with scale-dependent effects on natural enemies (Tscharntke et al 2007). Stable isotope ratios have been proven to be suitable for tracking the plant origin of herbivorous and predatory insects Vialatte et al 2006;Traugott et al 2008;Schallhart et al 2009Schallhart et al , 2011Forbes and Gratton 2011;Ouyang et al 2012). Recently, this method has been used to determine the dispersal of pest predators between alfalfa and maize in the northeast of the Iberian Peninsula (Madeira et al 2014).…”
Section: Introductionmentioning
confidence: 98%
“…The mark-recapture method is useful to estimate the abundance, survival rate, and dispersal ability of adult click beetles. Schallhart et al (2009) recently used the isotope ratio as a mark for estimating the dispersal of Agriotes beetles. Population parameters of M. okinawensis were first estimated by Kishita et al (2003).…”
Section: Okinawensismentioning
confidence: 99%
“…Since stable nitrogen ratios are influenced by human-induced environmental changes, stable carbon ratios may be useful to assess human cultivation of C 4 plants. One such study revealed that stable carbon ratios of target pests were able to indicate the distance from which cultivated C 4 plants could affect pests in habitats with uncultivated C 3 plants (Schallhart et al 2009). …”
Section: Introductionmentioning
confidence: 98%
“…For instance, A. cerana nests are often found in tree cavities in old growth forests (Oldroyd and Wongsiri 2006), and the workers are found near crop flowers in agricultural fields within mountainous and forested landscapes (Taki et al 2010). Apis cerana can also readily use holes in buildings, and populations are even found in highly disrupted human-dominant landscapes (Sasaki 1999). In the dense city of Hong Kong, A. cerana is often found and uses flowering plants for the majority of their food resources, and these plants are pollinated mainly by this honeybee species (Corlett 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation